2019
DOI: 10.1111/cpr.12688
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐130a controls bone marrow mesenchymal stem cell differentiation towards the osteoblastic and adipogenic fate

Abstract: Objectives With age, bone marrow mesenchymal stem cells (BMSC) have reduced ability of differentiating into osteoblasts but have increased ability of differentiating into adipocytes which leads to age‐related bone loss. MicroRNAs (miRNAs) play major roles in regulating BMSC differentiation. This paper explored the role of miRNAs in regulating BMSC differentiation swift fate in age‐related osteoporosis. Material and methods Mice and human BMSC were isolated from bone marrow, whose miR‐130a level was measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 54 publications
2
97
0
Order By: Relevance
“…Sun et al [24] found that miR-503 promotes bone formation in distraction osteogenesis by suppressing smurf1 expression. Lin et al [25] revealed that miR-130a controls bone marrow mesenchymal stem cell differentiation towards an osteoblastic and adipogenic fate. Until now, there has been no study on the role of miR-505 in the osteogenic differentiation of MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [24] found that miR-503 promotes bone formation in distraction osteogenesis by suppressing smurf1 expression. Lin et al [25] revealed that miR-130a controls bone marrow mesenchymal stem cell differentiation towards an osteoblastic and adipogenic fate. Until now, there has been no study on the role of miR-505 in the osteogenic differentiation of MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another putative target gene of miR-130a -PPARγexhibited only a trend towards significance in our experiments for a regulation by miR-130a. However, PPARγ regulation by miR-130a has been demonstrated in various organisms including humans [31,32,[40][41][42]. To the best of our knowledge our results are the first detecting AR and ADIPOQ as miR-130a target genes in the context of adipogenesis.…”
Section: Discussionmentioning
confidence: 62%
“…Vimalraj and Selvamurugan demonstrated that a significant upregulation of miR-130a, among others, was specific for differentiated osteoblast after 14 d in comparison to undifferentiated hMSCs [25]. Recently, Lin and colleagues demonstrated that miR-130a overexpression inhibits the adipogenic differentiation of murine bone marrow derived mesenchymal stem cells, while promoting the osteoblastic differentiation [32]. These results point towards an interference of miR-130a with early phases of adipogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…32 Moreover, miR-130a has also been unravelled to increase osteogenic differentiation and attenuate adipogenic differentiation of bone marrow mesenchymal stem cells. 33 In addition, Li et al have found that miR-130a inhibition protected rat cardiac myocytes from hypoxia-triggered apoptosis, 34 and it has been uncovered that miR-130a alleviated neuronal apoptosis and changes in expression of Bcl-2/Bax and Caspase-3 in cerebral infarction rats. 35 We conducted further experiments to discover that inhibited XIAP reversed the effect of suppressed miR-130a on MCAO rats and OGD-treated neurons.…”
Section: Discussionmentioning
confidence: 99%